Excitation of surface plasmons in thin noble metallic film of copper, silver and gold paper - Jaafar, M.; Othman, M.; Yaacob, M.; Haroon, H.; Ilyas, M. A.; Ayub, A. A. (2020)
The formation of surface plasmons in a different type of noble metallic film was successfully simulated using MATLAB program software. The thicknesses of copper, silver and gold metal films were varied between 20 nm to 80 nm. The narrowness and depth of surface plasmon resonance (SPR) curves were observed to determine the excitation of surface plasmons. The simulation results indicate that the maximum excitation of surface plasmons can be achieved by using silver thin film with thicknesses of 50 nm at the minimum reflectivity of 0.0038 a.u and full width at half maximum value of 0.2592°. The silver film that produces a deeper and sharper SPR curve has potential in the development of a low cost and high sensitivity of SPR sensing device.